MODEL KOMUNIKASI SOSIAL REMAJA MELALUI MEDIA TWITTER - Zikri Fachrul Nurhadi (Jurnal Aspikom)
This research aims to find out and explain the design, experience and sosial interaction in teenager sosial communication through Senior High School. The researcher applied the theory of fenomenology which explains the aware of experince structure togetherwith learning of experience type from the point of view for those people who directly get in touch. This research applied the qualitative method through observation, participant, in dept interview and preferences. This research subjects of the study were high school students as the main informant who represented by purposive sampling technique amounted to 17 people from three SMA Country in Ciamis districts. The result of this research shows that the design is divided in two designs, those are because design and for design. Because design uses the twitter for the development of environment and technology, easy to be used, entertaining, quick send and receive the message, borderless in place and time whereas for design is to get the up to date information, show the existence of them selves, make the social media for doing business, and find out new friends and relation. Whereas communication experience is divided in two, those are positive comunication and negative communcation. Positive communication experience describes the scope of wider twitter, information and promotion media whereas negative communication experience desribes the freedom posting, bad content, killing character and bad communcation. Whereas sosial interaction happens by sending and receiving message effectively, anxiety similarity and giving new cognition.